Peningkatan Kemampuan Berpikir Kritis Kreatif Siswa TKJ SMK Negeri 2 Seririt Melalui Pelatihan Robot Bioloid - Tjahyanti, Luh Putu Ary Sri; Adiarta, Agus; Gitakarma, Made Santo (Universitas Pendidikan Ganesha, 2019)
With the development of robotics technology in almost every area of human life, education and teaching the concept of robotics is expected to be included in the education curriculum in secondary schools. Technology Vocational Schools are expected to build robotics technology and practice it. One of the Technology Vocational Schools in Buleleng Regency, Bali, namely SMK Negeri 2 Seririt became a partner for the development of the Workshop and Entrepreneurship in Engineering (PKR) subject through the application of robotics training. This training uses Bioloid robots to improve creative critical thinking skills to students in the Computer and Network Engineering (TKJ) SMK Negeri 2 Seririt. The results obtained include students being very enthusiastic in participating in training, students increased understanding in assembling and programming robots as well as students' creative skills and critical thinking skills increased up to 72%.